Data for: Perceptions of Common Pool Resource Management in the Tana River, Norway: An Exploratory Analysis - Næss, Marius Warg; Fisktjønmo, Guro Lovise Hole; Bårdsen, Bård-Jørgen; Falkegård, Morten; Svenning, Martin (The Norwegian Institute for Cultural Heritage Research - NIKU, 2026)
The data reported here is based on the results from 1) interviews, 2) vignettes, and 3) an allocation game with fishers in the Tana River, Norway. The data was collected over two years, with the aim of collecting data from the vignettes in the winter of 2022/2023 and playing a follow-up game with the same participants in the spring of 2023. Participants were recruited from a list of active fishers provided by the Tana River Management (TF). However, while most of the participants in 2022 agreed to a follow-up in 2023 (one declined), eight of the 2022 participants were unreachable in 2023. Thus, seventeen participants played both the game and the vignettes in 2023, while seventeen did the vignettes in 2022 and the game in 2023 (one of the participants asked to be removed from the game after playing and was subsequently kept out of the analyses of the game). Nine participants have had or were in a position of trust (only one woman) in TF, the holders of the net fishing rights Tana (LBF) or as members of the fishing zone boards. See Table 1 in main text for descriptive data.

Datasetet bygger på resultat från intervjuer, vinjetter och ett fördelningsspel med fiskare i Tanaälven, Norge. För en mer detaljerad beskrivning av data och metod, se den engelska beskrivningen.
Data för: Perceptions of Common Pool Resource Management in the Tana River, Norway: An Exploratory Analysis
Keywords: ENVIRONMENTAL MANAGEMENT; MILJÖSTYRNING; COOPERATION; SAMARBETE; SUSTAINABILITY; HÅLLBAR UTVECKLING; Traditional ecological knowledge; Traditional ecological knowledge; Common pool resources; Common pool resources; Public Goods; Public Goods; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Social behaviour and attitudes; Socialt beteende och attityder; Environmental Sciences; Miljövetenskap; Ecology; Ekologi; Environmental Management; Miljöteknik och miljöledning; Fish and Aquacultural Science; Fisk- och akvakulturforskning; Social Anthropology; Socialantropologi; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap; Cultural Studies; Kulturstudier; Ethnology; Etnologi